Economic burden of hepatitis B infection among patients with diabetes. Issue 5 (3rd May 2016) - Deshpande, Gaurav; Klink, Andrew J.; Shenolikar, Rahul; Singer, Joseph; Eisenberg Lawrence, Debra F.; Krishnarajah, Girishanthy
ABSTRACT: Despite ACIP recommendation and cost-effectiveness established in those 19–59 y old diabetes patients the uptake of Hepatitis B vaccine in diabetes patients is low. There is need to highlight the impact of Hepatitis B virus (HBV) infection in diabetes patients in terms of healthcare utilization and costs to recognize the burden of HBV in this population. This retrospective claims analysis included patients with diabetes and HBV (cases; n=1, 236) and those with diabetes without HBV (controls; n=4, 944), identified by ICD-9-CM diagnosis codes. Cases were matched with 4 controls using propensity score matching. Healthcare utilization and cost were compared; incremental effect of HBV infection was assessed using multivariate analysis. In the adjusted analyses, the mean number of hospitalizations (0.6 vs 0.4), outpatient service visits (34.2 vs. 20.4), and office visits (10.9 vs. 9.8) were 41%, 68%, and 11% higher, respectively, in cases vs. controls (all p<0.05). Gastroenterologist visits (0.8 vs. 0.2) and infectious disease visits (0.1 vs. 0.0) were 80% and 18% higher in subset of case and controls with these events. Cases (39, 435) incurred 16, 397 incremental total costs compared with controls (23, 038). Medical (30, 968 vs. 17, 765) and pharmacy costs (8, 029 vs. 5, 114) were both significantly higher for cases (p < 0.0001). Healthcare utilization and costs were higher among patients with diabetes and HBV than in those with diabetes alone. These results provide evidence supporting the need for HBV vaccination among unvaccinated diabetes patients.